Análisis de la percepción de vulnerabilidad al cambio climático del cultivo de papa mediante la aplicación de la metodología cvca, en la comunidad de Pilacumbi, parroquia de Toacaso. - Fabara Valdiviezo, Anthony Samael (2023)
Climate change refers to the different processes or alterations in abiotic factors of the planet, such as temperature and precipitation, in known mutations in climate. This research analyzed the perception of vulnerability to climate change in potato cultivation (Solanum tuberosum) in Pilacumbi, parish of Toacaso, through the methodology known as CVCA (Analysis of capacity and climate vulnerability). This methodology allowed us to identify in the community of Pilacumbi the presence of climatic risks such as agricultural droughts, increase (July, August, January and February) and decrease in temperatures (frost). As well as non-climatic factors such as the increase in pests and diseases, the advance of the agricultural frontier and contamination of irrigation water. The resilience of potato cultivation (Solanum tuberosum) depends on climatic and non-climatic factors. This crop is already resilient in the community because it manages native species, live fences, and irrigation practices. It´s essential to recognize that to increase this climate resilience of the crop, several adaptation options must be realized both collectively and individually, focusing on actions, knowledge and training, resources, government roles, gender equality, ecosystems and inclusive governance.